Maternal immune activation alters temporal Precision of spike generation of CA1 pyramidal neurons by Unbalancing GABAergic inhibition intheOffspring - Griego, Ernesto; Cerna, Camila; Sollozo-Dupont, Isabel; Fuenzalida, Marco; Galván, Emilio J. (Brain, behavior, and immunity, 2025)
•LPS injection during pregnancy (MIA) increases cytokine production and decreases litter size.•MIA increases the temporal summation of EPSPs in hippocampal neurons.•MIA alters spatial summation and increases the probability of action potential discharge.•MIA alters the inhibitory/excitatory balance of CA1 pyramidal cells.•MIA alters the expression of GAD-positive interneurons.•MIA alters the performance of several behavioral tests in offspring. Infection during pregnancy represents a risk factor for neuropsychiatric disorders associated with neurodevelopmental alterations. A growing body of evidence from rodents and non-human primates shows that maternal inflammation induced by viral or bacterial infections results in several neurobiological alterations in the offspring. These changes may play an important role in the pathophysiology of psychiatric disorders like schizophrenia and autism spectrum disorders, whose clinical features include impairments in cognitive processing and social performance. Such alterations are causally associated with the maternal inflammatory response to infection rather than with the infection itself. Previously, we reported that CA1 pyramidal neurons of mice exposed to MIA exhibit increased excitability accompanied by a reduction in dendritic complexity. However, potential alterations in cellular and synaptic rules that shape the neuronal computational properties of the offspring remain to be determined. In this study, using mice as subjects, we identified a series of cellular and synaptic alterations endured by CA1 pyramidal neurons of the dorsal hippocampus in a lipopolysaccharide-induced maternal immune activation (MIA) model. Our data indicate that MIA reshapes the excitation-inhibition balance by decreasing the perisomatic GABAergic inhibition predominantly mediated by cholecystokinin-expressing Interneurons but not parvalbumin-expressing interneurons impinging on CA1 pyramidal neurons. These alterations yield a dysregulated amplification of the temporal and spatial synaptic integration. In addition, MIA-exposed offspring displayed social and anxiety-like abnormalities. These findings collectively contribute to understanding the cellular and synaptic alterations underlying the behavioral symptoms present in neurodevelopmental disorders associated with MIA.